2013
DOI: 10.1007/s11255-013-0602-0
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of cyclin D1 in renal cell carcinoma

Abstract: Cyclin D1 protein was overexpressed in RCC. The types of RCC appear to exhibit different immunohistochemical staining patterns for cyclin D1; high protein expression was related to good clinical outcome and to most known favorable prognostic factors. Further investigations are necessary to reveal which mechanisms lead to cyclin D1 accumulation in neoplastic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…In renal cell cancer, CCND1 was absent in normal kidney samples but overexpressed in RCC. High CCND1 expression was related to good clinical outcome and to most known favorable prognostic factors [29]. Moreover, high CCND3 protein was observed in 16% of the tumors and was significantly associated with high TNM stage, high nuclear grade, high proliferation and young age [30].…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell cancer, CCND1 was absent in normal kidney samples but overexpressed in RCC. High CCND1 expression was related to good clinical outcome and to most known favorable prognostic factors [29]. Moreover, high CCND3 protein was observed in 16% of the tumors and was significantly associated with high TNM stage, high nuclear grade, high proliferation and young age [30].…”
Section: Discussionmentioning
confidence: 99%
“…Hedberg et al [31] examined the protein contents in tissues of human ccRCC, and overexpression of Cyclin D1 and Cyclin E were observed. Similarly, Lima et al [32] and Nauman et al [33] showed the high levels of Cyclin D1 and Cyclin E protein in human ccRCC. in cell experiments, researchers found that decreased Cyclin D1 and Cyclin E could inhibit the proliferation of RCC cells [34,35].…”
Section: Discussionmentioning
confidence: 81%
“…higher levels of cyclin D1 are correlated with tumor size, Fuhrman grade and indicate poor prognosis for patients. 35 Elevated expression of cyclin E was observed in ccRCC tumors; level of cyclin E is correlated with loss of differentiation, increased aneuploidy and higher tumor grade. 36,37 As could be predicted, faster proliferating cells with silenced GRHL2 expression have reduced levels of cell cycle inhibitors p21 and p27.…”
Section: Discussionmentioning
confidence: 98%